‘Hey, Jude! I Wanna Hold Your Hand’: Transitivity Process Analysis on Popular Songs by The Beatles - Shamsul, Harbi; Mohd Shafiq, Abdul Jabar; Alia Najaa, Md Nor; Nursyaheedah, Muhammad Isa (Universiti Malaysia Pahang, 2019)
Needless to say, The Beatles is the most popular rock band in the world. Their huge popularity has sparked a phenomenon known as ‘Beatlemania’. In 2001, the Guinness World Records acknowledged The Beatles as the best-selling group for their achievement for selling more than 1 billion units worldwide. Thus, this paper attempts to reveal how language is used in widely recognized songs by The Beatles from the transitivity perspective, primarily, the process. Halliday (1994) proposes six different transitivity processes which are material, mental, relational, verbal, behavioral and existential. Ten popular songs by The Beatles are selected in this study. Unlike other prior studies done on transitivity to various types of literature, this study is different due to its unique data set which is The Beatles’ popular songs. By focusing on the process according to the different types of processes in the experiential metafunction, this study reveals how The Beatles employs different processes in their lyrical writing of their popular songs in order to communicate their experiences of the world.